Fluorides in the Environment Effects on Plants and Animals - Weinstein, L. H.; Davison, A. W.; Ebooks Corporation (Wallingford : CABI, 2004)
Weinstein (Cornell U., US) and Davison (U. of Newcastle, Britain) provide background material on the natural and artificial occurrence of the element and its impact on biological beings, in order to inform the perennial debate about adding fluoride to public water systems. Among their topics are sou
Contenido: Preface; Acknowledgements; 1 The History of Fluorine and Sources of Fluorides in the Environment; 2 Uptake, Transport and Accumulation of Inorganic Fluorides by Plants and Animals; 3 Effects of Inorganic Fluorides on Animals; 4 Effects of Inorganic Fluorides on Plants and Other Organisms; Colour Plates; 5 Some Case Histories Involving Fluoride Contamination; 6 Monitoring and Identifying Effects of Fluoride in the Field; 7 Environmental Standards to Protect Humans, Other Animals and Plants; 8 Natural Organofluorine Compounds; 9 Manufactured Organofluorine Compounds; References; Index
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: FLUORUROS -- ASPECTOS AMBIENTALES